CONTESTATION FOR ANNULMENT COMMON IN THE REGULATION OF THE NEW CODE OF CIVIL PROCEDURE - Licuta, PETRIA (Strategii Manageriale, 2014)
Contestation for annulment whatever its form, is an extraordinary means of appeal that is exercised according to art.503-508 of the new code of civil procedure, only for the reasons and under the conditions laid down by the legislator. Contestation for annulment allows the party that is interested to challenge a final judgment given in violation of procedural rules. The paper addresses theoretical issues, of the common appeal for annulment, being analyzed aspects aimed at the parties, the object, the exercise period and settlement procedure, of this remedy available to the interested party.